PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KERINCI - Riswanto Bakhtiar (LPPM Universitas Ekasakti, 2020)
This study aims to reveal the effect of work motivation on employee performance at the Department of Population and Civil Registration of Kerinci Regency. This study uses quantitative methods, with exogenous variables, namely the work motivation variable, employee performance at the Department of Population and Civil Registration, Kerinci Regency. The data collection technique in this study used a proportional stratified random sampling technique. The population of this study were all employees at the Department of Population and Civil Registration of Kerinci Regency. Respondents in this study amounted to 96 samples. The data analysis technique used is path analysis and is divided into 2 paths, namely sub-structure 1 and sub-structure 2. Data is collected through a questionnaire that has been tested for its validity and reliability in advance both in terms of content and empirical test of items in the field. The results of this study have found that the hypothetical model is proven to be used as a new model in improving the performance of employees at the Department of Population and Civil Registration of Kerinci Regency. The findings in this study indicate that: There is an effect of work motivation on performance.